Mapping Resonance Structures in Transient Core-Ionized Atoms - Mazza, T.; Ilchen, M.; Kiselev, M. D.; Gryzlova, E. V.; Baumann, T. M.; Boll, R.; De Fanis, A.; Grychtol, P.; Montaño, J.; Music, V.; Ovcharenko, Y.; Rennhack, N.; et al. (My University, 2020)
The nature of transient electronic states created by photoabsorption critically determines the dynamics of the subsequently evolving system. Here, we investigate K-shell photoionized atomic neon by absorbing a second photon within the Auger-decay lifetime of 2.4 fs using the European XFEL, a unique high-repetition-rate, wavelength-tunable x-ray free-electron laser. By high-resolution electron spectroscopy, we map out the transient Rydberg resonances unraveling the details of the subsequent decay of the hollow atom. So far, ultra-short-lived electronic transients, which are often inaccessible by experiments, were mainly inferred from theory but are now addressed by nonlinear x-ray absorption. The successful characterization of these resonances with femtosecond lifetimes provides the basis for a novel class of site-specific, nonlinear, and time-resolved studies with strong impact for a wide range of topics in physics and chemistry.